THU0433 A Study of 101 Septic Arthritis: Debridement and not Debridement. (23rd January 2014) - Riveros, A.; Mateo, L.; Martínez-Morillo, M.; Tejera, B.; Rodríguez, S.; Sanint, J.; Holgado, S.; Cañellas, J.; Tena, X.; Olivé, A.; Giménez, M.
Abstract : Objectives: To describe the clinical, microbiological characteristics and evolution of pyogenic arthritis according to treatment. Methods: Design retrospective (1984-2012). Hospital: academic terciary hospital. Referral area 800.000. We reviewed the medical records of patients with pyogenic arthritis from the database of the Rheumatology Department. The inclusion criterion was the isolation of bacteria in the culture of joint fluid or blood cultures. Soft tissue infection, prosthetic infection, spondylodiscitis, fungal and mycobacterial arthritis were excluded. Results: We selected a total of 101 cases. Thirty four cases (33.6%) underwent surgical debridement and the remaining 67 (66.4%) were treated medically (Table 1 ). All patients received specific intravenous antibiotic, with an average duration of three weeks. Surgical treatment (bursectomy in 2 cases, arthrotomy in 31 cases and amputation in 1 case) was required in 34 cases (intervention before 7 days in 18 (53%) patients, arthrotomy within 48 hours in 9 patients). A second arthrotomy was required in 3 patients (9%). Moreover, articular lavages were performed daily in 35 cases (51%) of the 67 patients without arthrotomy. There were 14 deaths among the patients who were not debrided and one death in the group of patients that were surgically debrided. Of the patients who died, 5 had monoarticular involvement (knee) and 7 cases had polyarticular involvement. The causative organisms in these patients were S. Aureus (7 cases), MRSA (3 cases), Pneumococcal (1 case), E. coli (1 case), polymicrobial (1 case of S. aureus and E. coli). Conclusions: The mortality of the patients with septic arthritis that were debrided was much lower than those not debrided. The history of arthroscopy or arthrocentesis before septic arthritis was more common among patients that were debrided. Patients with greater diagnostic delay needed debridement more frequently. Disclosure of Interest: None Declared